Design and Simulation of a Combined Displacement Amplification Mechanism - Xueyuan Rong; Hong Zhou; Chunlin Guan (Jixie chuandong)
Bridge-type displacement amplifier is usually used to amplify the output displacement of the piezoelectric ceramic actuator in a micro-displacement positioning system which driven by a piezoelectric ceramic actuator. In order to obtain a higher displacement magnification and solve the problem of parasitic displacement due to poor installation of the bridge-type mechanism， a two-stage displacement amplification based on flexible hinges is designed， which combined a bridge-type mechanism with two symmetrically arranged Scott-Russell mechanisms. The statics model of the mechanism is established based on method of stiffness matrix， the calculation formulas of amplification ratio and stiffness of mechanism are obtained accordingly. The dynamics model and the inherent frequency of the mechanism are established by Lagrange dynamics equation， the finite element simulation method is performed to verify the correctness of models. The results show that the amplification ratio of the combined mechanism is 6.11 and the input stiffness is 12.58 N/μm， the output stiffness is 0.11 N/μm， the natural frequency is 532.52 Hz， which are basically consistent with the theoretical value， and the relative errors are within 10%. The results meet the design requirements.